Dear John - Sparks, Nicholas (Sphere, Warner Books, 2010)
John, a high school dropout, enlists in the Army not knowing what else to do with his life. While in the Army he meets Savannah, they fall in love and she awaits his return from the Army. After 9/11 John feels it's his duty to re-enlist. During their long separation Savannah falls in love and marries someone else.